2014
DOI: 10.1117/12.2042261
|View full text |Cite
|
Sign up to set email alerts
|

Threshold power and fiber degradation induced modal instabilities in high-power fiber amplifiers based on large mode area fibers

Abstract: We report on two types of modal instabilities observed in high power Yb amplifiers based on Large Mode Area Fibers. The first is observed to occur at a Threshold Power, which we refer to as Threshold Power Modal Instabilities (TPMI). The modal instability is observed as a decrease in beam quality or reduced core light output as higher order modes leak into the fiber cladding. In PM 25/400 fiber amplifiers, we observe the threshold for the modal instability to vary depending on pump wavelength detuning, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 16 publications
(24 reference statements)
5
60
2
Order By: Relevance
“…The lengths of the fibers are adjusted the minimum value necessary to achieve high efficiency, defined as pump absorption ≈0.95. It shows that threshold power is dependent on pump wavelength, and by shifting the pump wavelength from 976nm to 970nm or 985nm, the threshold power can be increased by 40% or 80%, respectively, which agrees with experimental reports [17]. According to Eq.…”
Section: Numerical Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The lengths of the fibers are adjusted the minimum value necessary to achieve high efficiency, defined as pump absorption ≈0.95. It shows that threshold power is dependent on pump wavelength, and by shifting the pump wavelength from 976nm to 970nm or 985nm, the threshold power can be increased by 40% or 80%, respectively, which agrees with experimental reports [17]. According to Eq.…”
Section: Numerical Resultssupporting
confidence: 89%
“…2 (b): although the peak core heat load at 915nm is larger than 920nm, the threshold at 915 is higher than that at 920nm; the peak core heat load at 965nm is smaller than that at 960nm, but the threshold at 965 is lower than that at 960nm; at other pump wavelength, larger peak core heat load indicates lower threshold power. This means that heat load may not have any relation with the MI threshold power as claimed in [17]. Detailed theoretical investigation indicates that the portion of the heat profile that is responsible for mode coupling gain is the antisymmetric part created by the antisymmetric part of the signal irradiance [25], where the antisymmetric part is created due to the high order mode.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Similar to the observation in [20], the instability of MI has a grown-process: at the start (T1), only background noise increase, which means stable beam profile and indicate that MI may relate to noise [14]; after a few seconds (T2), frequency components shown up, which indicates unstable beam profile. After multiple power cycles near the maximum power, we observed that the threshold reduced to below 1.2kW, which may due to the fiber degradation [5,21]. …”
Section: Experimental Setup and Resultsmentioning
confidence: 88%
“…Most of the high power fiber laser systems with random polarized output are based on MOPA at the moment, which has achieved output power as high as tens of kilowatt. However, power scaling of linearly-polarized MOPAs to multi-kilowatt level is currently limited by the onset of mode instabilities (MI) [4][5][6]. Although lot of work has been carried out to deal with MI experimentally and theoretically [7][8][9][10][11][12][13][14][15][16][17][18][19], few methods to mitigate MI effectively in all-fiber MOPA configuration with standard step-index large mode area (LMA) fiber have been proposed, and MI-free power scaling in all-fiber MOPA, which are based on standard stepindex PM LMA fibers, is even more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Typical mode instability threshold powers are several hundred watts to a few kilowatts [1][2][3][4][5]. Previous work has explained how to maximize the threshold by minimizing seeding of the higher order mode by either eliminating amplitude modulation of the pump and signal [8,11], or by minimizing spontaneous thermal Rayleigh scattering [12].…”
Section: Introductionmentioning
confidence: 99%